The communicative effectiveness of section 3.3 of the benefits policy (DV0406) of Stellenbosch University (SU) after rewriting it into plain language and according to document design principles - Gabriels, Carmen Allison Pamela (Stellenbosch : Stellenbosch University, 2020)
Thesis (MA)--Stellenbosch University, 2020.